Associated effects of shift work on productivity and health in outbound call center operations - Dela Cuesta, Lualhati M. (2004)
The study investigated the associated effects of individual attributes (age and gender) and shift work options (shift type, shift length, shift time-in sequence, work-rest day ration) on the productivity and health of a sample size of outbound agents in a call center in the Philippines. The individual attributes, being inherent in the respective agents, and shift work options as management decisions were tested alongside one another in the prediction of the outcome measures of: